Dirāsat fī al-Islām al-Mahallī: Adwā’ ‘alā Inṣihār al-Islām fī al-Thaqāfah al-Jāwīyah - Hilmy, Masdar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This article attempts to explore a study of Islam in Java in the frame of the above conception -the dialogue tradition. The process of acculturation between Islam and Javanese culture, which developed in the dialogue tradition, is the central point of this article. Religious discourses embodied in Javanese texts, such as suluk and babad, written in the period of the establishment of Islam until the 19th century, are considered as the cultural representation of the fault line -despite the harmonious reconciliation- between Islam and Javanese tradition. In this context, changes in social and political affairs in Javanese courts, especially crucial changes in the 19th century following the colonialism, implanted the emergence of religious discourses embedded in the Javanese texts observed in this article.DOI: 10.15408/sdi.v7i2.712